The Pedagogy of Intelligent Systems: Integrating AI ınto Future-Oriented English Language Learning - Xiaoying, Feng; Ruiqian, Su (European Journal of Social Science Education and Research, 2026)
The article explores the use of intelligent systems and in particular Artificial Intelligence (AI) in English language teaching, yet with a particular focus on building a socio-technical framework of the pedagogy in the future. The study explores the way in which the newest technologies, such as AI based adaptive learning systems, Virtual Reality (VR), Augmented Reality (AR), and multimodal learning tools, can be applied to enhance language learning through offerings of personalized learning pathways, real-time information and immersion. Such intelligent mechanisms prove to be very effective in terms of learner engagement, motivation and language proficiency as compared to the traditional mechanisms such as textbook learning, lecture-based teaching and role-playing. The article discusses how AI-driven systems, such as speech recognition and interactive VR/AR simulations, can be effective in improving such skills as pronunciation, analysis, and practical language use in real-life situations. The results indicate that AI-based adaptive learning, gamification, and immersive environments can provide more scalable, efficient, and dynamic learning experiences compared to traditional techniques.